2008
DOI: 10.1002/pssb.200844238
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐induced structural phase transitions in materials and earth sciences

Abstract: Pressure is an important thermodynamic parameter since it allows an increase of matter density by reducing volume. The reduction of volume by applying high pressures leads to an overall decrease of interatomic and intermolecular distances that allows exploring in detail atomic and molecular interactions. Therefore, high‐pressure research has improved our fundamental understanding of these interactions in solids, liquids and gasses. The study of the structure of matter under compression is a rapid developing fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 307 publications
0
48
0
3
Order By: Relevance
“…On the other hand, (ii) high tensile strain allows one to imagine that the dislocation region is under less positive or negative pressure compared to the bulk. In the field of high pressure experiments, there is an interesting tendency known as so-called pressure-coordination rule [19]. In the case of some perovskite and the related compounds [20,21], ilmenite crystal structure that is stable under lower pressure transforms into perovskite under higher pressure.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, (ii) high tensile strain allows one to imagine that the dislocation region is under less positive or negative pressure compared to the bulk. In the field of high pressure experiments, there is an interesting tendency known as so-called pressure-coordination rule [19]. In the case of some perovskite and the related compounds [20,21], ilmenite crystal structure that is stable under lower pressure transforms into perovskite under higher pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The standard B3LYP hybrid method has been extensively used for molecules and also provides an accurate description of crystalline structures as bond lengths, binding energies, and band-gap values are regarded. 29,30 The diagonalization of the Fock matrix was performed at adequate k−point grids in the reciprocal space (Pack-Monkhorst 1976) of shrinking parameters 4-6 depending on the phase being treated (8,18,27, and 27 k points for sernamontite, β-Bi 2 O 3 -type, γ -Sb 2 O 3 , and valentinite-type phases, respectively). The thresholds controlling the accuracy of the calculation of Coulomb and exchange integrals were set to 10 −8 and 10 −14 assuring a convergence in total energy better than 10 −6 a.u.…”
Section: Theoretical Detailsmentioning
confidence: 99%
“…These studies have shown the complex nature of the phase transitions in these sesquioxides and the need to study the pressure-induced phase transitions in other polymorphic phases of these compounds in order to better understand their similarities and differences with respect to other sesquioxides. 18 In this work, we present a structural and vibrational study of senarmontite up to 25 GPa by means of x-ray diffraction (XRD) and Raman measurements which are complemented with total-energy and lattice-dynamics calculations in the framework of density-functional theory (DFT). We will show that, unlike arsenolite, senarmontite remains in the cubic structure up to 25 GPa and that it suffers two isostructural phase transitions at 3.5 and 10 GPa, respectively, in which senarmontite loses its molecular character to become a threedimensional solid.…”
Section: Introductionmentioning
confidence: 99%
“…1 In particular, orthophosphates ͑APO 4 ͒ are relevant in mineral physics and chemistry and very important for petrology studies. 2 Additionally, they have a wide potential for their application in optoelectronics due to their optical and luminescent properties.…”
Section: Introductionmentioning
confidence: 99%